Socioeconomic status and ischaemic heart disease mortality in 10 western European populations during the 1990s. Issue 4 (10th October 2005) - Avendano, M; Kunst, A E; Huisman, M; Lenthe, F V; Bopp, M; Regidor, E; Glickman, M; Costa, G; Spadea, T; Deboosere, P; Borrell, C; Valkonen, T; et al.
Abstract : Objective: To assess the association between socioeconomic status and ischaemic heart disease (IHD) mortality in 10 western European populations during the 1990s. Design: Longitudinal study. Setting: 10 European populations (95 009 822 person years). Methods: Longitudinal data on IHD mortality by educational level were obtained from registries in Finland, Norway, Denmark, England/Wales, Belgium, Switzerland, Austria, Turin (Italy), Barcelona (Spain), and Madrid (Spain). Age standardised rates and rate ratios (RRs) of IHD mortality by educational level were calculated by using Poisson regression. Results: IHD mortality was higher in those with a lower socioeconomic status than in those with a higher socioeconomic status among men aged 30–59 (RR 1.55, 95% confidence interval (CI) 1.51 to 1.60) and 60 years and over (RR 1.22, 95% CI 1.21 to 1.24), and among women aged 30–59 (RR 2.13, 95% CI 1.98 to 2.29) and 60 years and over (RR 1.36, 95% CI 1.33 to 1.38). Socioeconomic disparities in IHD mortality were larger in the Scandinavian countries and England/Wales, of moderate size in Belgium, Switzerland, and Austria, and smaller in southern European populations among men and younger women (p < 0.0001). For elderly women the north–south gradient was smaller and there was less variation between populations. No socioeconomic disparities in IHD mortality existed among elderly men in southern Europe. Conclusions: Socioeconomic disparities in IHD mortality were larger in northern than in southern European populations during the 1990s. This partly reflects the pattern of socioeconomic disparities in cardiovascular risk factors in Europe. Population wide strategies to reduce risk factor prevalence combined with interventions targeted at the lower socioeconomic groups can contribute to reduce IHD mortality in Europe.